Efektivitas Putusan KPPU dalam Mencegah Praktik Monopoli dan Persaingan Usaha Tidak Sehat - Dian Nukhidah Zurny; Rodiatun Adawiyah; Muhammad Arif Prasetyo (Fakultas Hukum Universitas Riau, 2026)
Monopolistic practices and unfair business competition constitute serious challenges to the national economic system, as they undermine market efficiency, harm public interests, and create inequality among business actors. To prevent and address such practices, the Indonesian government established the Komisi Pengawas Persaingan Usaha (KPPU) as an independent institution authorized to enforce competition law. This study aims to analyze the effectiveness of Decision Number 03/KPPU-I/2024 in preventing monopolistic practices and unfair business competition, as well as to assess the extent to which the decision provides legal certainty and deterrent effects for business actors. This research employs a normative legal research method using a statutory approach and a case approach. The data consist of primary, secondary, and tertiary legal materials, which are analyzed qualitatively. The analysis focuses on the legal reasoning of the Commission Panel, the assessment of evidentiary elements, and the administrative sanctions imposed in Decision Number 03/KPPU-I/2024. The findings indicate that Decision Number 03/KPPU-I/2024 has, in principle, fulfilled the elements of competition law enforcement as stipulated in Law Number 5 of 1999. The legal considerations applied by the Commission Panel reflect an effort to uphold the principles of fair competition and protect public interests. However, the effectiveness of the decision in preventing monopolistic practices and unfair business competition remains limited, particularly in relation to the enforcement of sanctions and the level of compliance by business actors. Therefore, strengthening the execution mechanism of KPPU decisions and enhancing institutional coordination with the judiciary are necessary to improve the effectiveness of competition law enforcement in Indonesia.